Ad-Dakhil Bi Al-Isyarah dalam Kitab Qayyum Al-Asma’ Karya Shirazi: Kajian Terhadap Bentuk dan Penyimpangannya - Ilham Abiyusuf; Fadhli Maulana Ihsan; Pakhrurrozi Pakhrurrozi; Lukmanul Hakim; Nixon Nixon (Khazanah : Journal of Islamic Studies, 2026)
The emergence of new religious movements such as Bábism, which claim to have alternative sources of revelation outside the Qur'an, particularly through the Qayyum al-Asma' by Sayyid 'Ali Muhammad Shirazi (the Báb). The aim of this study is to identify and analyze forms of deviant esoteric interpretation (ad dakhil bil isyarah) in this book, specifically in Surah 93 pages 192-193, and to compare them with interpretations from mainstream Qur'anic exegesis (tafsir). The research employs a qualitative method with a library research approach and descriptive-analytical design. Data collection was conducted by tracing and recording texts from the original manuscript of Qayyum al-Asma', while data analysis used content analysis and comparative analysis through five steps: identifying the Báb's claims, describing his interpretation, collecting comparator interpretations, comparative analysis, and ad dakhil bil isyarah analysis. The findings reveal three forms of ad dakhil bil isyarah deviation in Qayyum al-Asma': the symbol of qamis (shirt) claimed as a medium for transmitting spiritual authority and blood as a sacrament of salvation; the symbol of al-nahl (bee) transforming honey into an "elixir" of life; and the symbol of al-nar wa al-nur (fire and light) at Mount Thur, where the Báb claimed himself as the entity that spoke to Prophet Moses. These three deviations contradict the authoritative interpretations of Ibn Kathir, Al-Qurtubi, Al-Mishbah, Jalalain, and the Indonesian Ministry of Religious Affairs.